2010
DOI: 10.5194/we-10-38-2010
|View full text |Cite
|
Sign up to set email alerts
|

Resin production in natural Aleppo pine stands in northern Evia, Greece

Abstract: We investigated the variability in resin yield of Aleppo pines in Evia (Greece) with the aim to exploit this natural resource in a sustainable way. Ten experimental plots were established in natural pine stands for monitoring. Our results revealed significant differences among stands, with high variation among individual trees in each plot. Maximum resin production was achieved in the Livadakia site whereas the minimum was obtained in Kokinomilia. All trees were classified according to their resin production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 6 publications
2
18
0
2
Order By: Relevance
“…Zanski (1970) reported that resin productivity is influenced by a number of factors: soil, climate, the use of chemicals, tree age, silvicultural treatments, and tree genetics. Spanos et al (2010) found a low correlation between the height of trees and the amount of resin productivity at a value of R 2 =0.315. Therefore, it could be concluded that the height of a tree does not have a correlation to its resin productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zanski (1970) reported that resin productivity is influenced by a number of factors: soil, climate, the use of chemicals, tree age, silvicultural treatments, and tree genetics. Spanos et al (2010) found a low correlation between the height of trees and the amount of resin productivity at a value of R 2 =0.315. Therefore, it could be concluded that the height of a tree does not have a correlation to its resin productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the stimulant ETRAT which contains ethylene and citric acid could increase resin productivity by activating the ethylene in the plant which will stimulate exudation of resin (Santosa 2011). The study conducted by Spanos et al (2010) used a stimulant paste which consisted of sulfuric acid, water, and kaolin to increase resin productivity. However, the factor that strongly determines resin productivity is the tree's optimum ability to produce pine resin (Sukadaryati and Dulsalam 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Referring to various studies [9,10], the models were constructed base on the regression between resin productivity with stand's parameters such as diameter, height and harvest intensity. The intensity of harvesting is a function of the number of tapping points measured and the accumulation of scars due to tapping.…”
Section: Discussionmentioning
confidence: 99%
“…The stand age can only explain 49.9% of the total height, whereas the remaining 51.1% of height can be affected by other variables. The R 2 adj = 55.7 on the equation (9), it consequences that height variance is only 57.7% influenced by diameter. Different to diameter, stand height is not affected by silviculture treatments such as stand density.…”
Section: Growth Of Diameter and Heightmentioning
confidence: 99%
“…These results were similar with the findings of many researchers 20 . Resin production is also affected by genotype and environmental interaction 23 . …”
Section: Resin Ductsmentioning
confidence: 99%